The Impact of New Coronavirus on Cancer Patients - Aida Karimian; Sona Talaei; Arash Abdolmaleki; Asadollah Asadi; Muhammad Akram; Hussein A. Ghanimi (Research Center for Rational Use of Drugs (RCRUD), 2021)
At the end of 2019, a new coronavirus (severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)) emerged in China and then spread worldwide. Presently, Coronavirus Disease 2019 (COVID-19) is a main public health issue. As of August 2021, more than 200 million confirmed cases from coronavirus and more than 4 million deaths have been reported by WHO in 222 countries. The data sources are Google Scholar, PubMed, and Science Direct articles. Publications were searched without regard to time in order to obtain a holistic and comprehensive perspective of the research done on this issue thus far. The SARS-CoV-2 can be transmitted from the human-to-human by respiratory droplets and shows great potential for a pandemic. Therefore, on March 11, 2020, COVID-19 was introduced as a global pandemic by WHO. Cancer patients are at high risk for exposure to the coronavirus. In the present article, we discuss the impact of the COVID-19 pandemic on the quality of life of cancer patients and their treatment process. One of these challenges is not visiting the patients in medical centers and hospitals for afraid of contracting the virus. Therefore, the diagnosis and treatment of cancer patients may be delayed, which is a serious threat to the lives of cancer patients. In this article, in addition to the impact of coronavirus on the lives of cancer patients, the severity of the disease in these patients, their required medical care, and the vaccination process are discussed.